A Clinical Informatics Program Directors' Proposal to the American Board of Preventive Medicine - Pageler, Natalie M.; Elkin, Peter L.; Kannry, Joseph; Leu, Michael G.; Levy, Bruce; Lehmann, Christoph U. (Applied Clinical Informatics, 2020)
In 2013, the American Board of Preventive Medicine (ABPM) and the American Board of Pathology (ABPath) offered the first board certification examination in Clinical Informatics to eligible physicians in the United States. In 2022, the Practice Pathway will expire and in 2023 only candidates eligible through the Fellowship Pathway will be eligible for the board certification. To date, Clinical Informatics as a specialty has not had a regular match process and used a controlled offer-acceptance process that does not meet candidates' or programs' needs. Fellows may not be offered a position with their top choice program initially, and they may accept offers from other programs to avoid risk by ensuring that they have a fellowship position. Programs have to consider losing an applicant in the first round in the ranking of applicants. The process is open to manipulation including early agreements between program directors and candidates. In this open letter to the ABPM, program directors make the case for a third-party match and are calling on the ABPM to leverage its status as the Clinical Informatics certifying body and its existing infrastructure to implement a Clinical Informatics match.
Keywords: clinical informatics; professional training; education; physician; general healthcare providers; training and education requirements; health care; accreditation and licensure; Clinical Informatics Fellowship